Private finance initiative (PFI): concept and method of procurement for construction projects - Abdul Rashid, Khairuddin (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2007)
In 2006 Malaysia embarked on using Private Finance Initiative or (FPI) as one of the methods to procure public building and infrastructure development projects. Procurement under PFI is significantly different from the conventional approach and there is a growing body of literature on the subject of PFI. In the context of Malaysia, most of the literature is not necessarily applicable and valid at all times.